Pip Street : A Crummpety calamity. - Simmons, Jo.; Wells, Steve (London : Scholastic Children's Books, 2013)
When Bobby's dad becomes the manager of the local crumpet factory, Bobby thinks his moving worries are at last over. He likes it here on Pip Street. Except no one is buying crumpets! Unless someone comes up with a fantabulous plan to make them more interesting, Bobby's dad might lose his job and that means ... uh-oh ... moving again!
3-6.
Turkish.